Exploring the impact of collaboration on the implementation of disaster governance - Oscar Radyan Danar; Asti Amelia Novita (Cogent Social Sciences)
The effective disaster governance plays an essential role in enhancing resilience organising prompt evacuations and delivering assistance to impacted areas is apparent. Within the context of Lumajang, this approach often involves through multi-agency collaboration to reducing casualties and mitigating the overall impact of the eruption on residents and infrastructure. The primary goal of this study is to explore the impact of the collaboration process during the implementation of disaster governance, and to explain and explore the mutual and nonlinear interaction between them. This inquiry was conducted in the Lumajang Regency, an Indonesian disaster-prone area. In this study, we also propose a questionnaire-based partial least squares structural equation model (PLS-SEM) with multiple latent variables: disaster governance (X), collaboration process (Y), and impact on community (Z). The results of this study found that collaboration has a direct impact on several aspects of disaster governance implementation, especially in terms of transparency enhancement. This confirms that collaboration is an effective way to build mutual commitment and a shared understanding to increase transparency and accountability principles. However, this finding also reveals that some of the collaboration aspects are difficult to perform under disaster governance implementation because of several reasons such as historical background, past experiences, or limited capacity of the implementing agency.